Budgetary allocations and government response to COVID-19 pandemic in South Africa and nigeria - Agunyai Samuel Chukwudi; Ojakorotu Victor (Journal of Risk and Financial Management, 2022)
The eruption of the novel virus brought to the global scene the prediction that Africa would be worse hit by the pandemic. This prediction was partly built on the widely recognized fact that Africa is the continent with the weakest public health care system and the lowest budgetary allocations to health. However, contrary to this prediction, the COVID-19 death rate in Africa has been low compared to in other continents. Debates on Africa's low COVID-19 death rate have generated mixed reactions, the majority of which have centred on beliefs and superstition about hot weather and Africa's youth-dominated society. Little or none of these reactions have attributed the low COVID-19 death rate to swift and prudent budgetary adjustment, which partly aided a swift response from some African governments. Indeed, not many studies have examined the swiftness in the response of some African governments and prudent budgetary adjustment in tackling the spread of COVID-19. This paper, through secondary data, advances knowledge on how budget revision aided government response to the COVID-19 pandemic in South Africa and Nigeria. It found that both countries adjusted their budgetary allocations in response to COVID-19. It further indicates that South Africa, through budgetary revision, allocated more funds to government agencies in charge of COVID-19 and various relief packages than Nigeria. Moreover, it indicates that the swift budgetary adjustment by both countries partly aided a quick government response that progressively flattened the curve and, in the long run, partly contributed to fiscal impulse and deferrals.
Keywords: 650; allocation; budgetary; COVID-19; pandemic; response